Canadian Academy of Sport and Exercise Medicine position statement: Neuromuscular training programs can decrease anterior cruciate ligament injuries in youth soccer players - Campbell, C. J.; Carson, J. D.; Diaconescu, E. D.; Celebrini, R.; Rizzardo, M. R.; Godbout, V.; Fletcher, J. A.; McCormack, R.; Outerbridge, R.; Taylor, T.; Constantini, N.; Cote, M. (Clinical Journal of Sport Medicine, 2014)
This Canadian Academy of Sport and Exercise Medicine (CASEM) position statement reviews the literature and concludes that youth soccer players and their coaches can decrease the incidence of anterior cruciate ligament (ACL) injuries of the knee through the implementation of neuromuscular training (NMT) programs. Furthermore, we propose a coordinated Canada-wide adoption of such injury prevention programs.